Meridian Flow Analysis in Axial Multistages Turbomachinery: Case of Gas Turbine Design - Belkacem, Bendjaima (Techniques and Innovation in Engineering Research Vol. 6, 2022)
To the present study develop a meridian flow model in the axial multi stages turbo machinery with compressible fluid. The flow equations are identical to those in the free vortex configuration and outside the blade zone in the case of single stage axial machines. A specific analytical resolution was developed, first treating an ideal machine and then a real gas turbine in two stages, where the reception essays of the machine in question, an analysis on the essays of the real machine was carried out to validate the selected analytical resolution. The method carried made it possible to calculate a scale factor of design of new machines from an initial machine. The calculation is validate with a numerical resolution (calculation by finites differences is carried out in this study). The approximate calculation is confirmed in this study and it will be possible to carry out program by using data-processing tools in order to facilitate the study of the flow in the machines in question and to allow to the engineer the exploitation of our study with simpler and more practical methods.